Patient with severe fever with thrombocytopenia syndrome virus infection and central nervous system disturbance in Dongyang, Zhejiang Province, China, 2017 - Yi Sun; Bin Guo; Hao Yan; Ai Lan Wu; Wen Wu Yao; Kang Chen; Jun Hang Pan; Zhao Xia Li; Hai Yan Mao; Yan Jun Zhang (Virology Journal, 2019)
Abstract Background Severe fever with thrombocytopenia syndrome (SFTS) is an emerging hemorrhagic fever that was first described in China in 2011. We report a patient who died of Severe fever with thrombocytopenia syndrome virus (SFTSV) infection, with a rapidly progressive central nervous system (CNS) disturbance, in Dongyang, Zhejiang Province, China, in 2017. Case presentation A 64-year-old man was admitted to hospital after 4 days of fever. SFTSV was detected 1 day after the patient was admitted to hospital. The patient presented with CNS disturbance and died 4 days after admission. Detailed clinical and epidemiological investigations and laboratory tests were conducted. Reduced platelet, white blood cell, lymphocyte, and neutrophil counts, elevated lactate dehydrogenase, creatine kinase, aspartate aminotransferaseand alanine aminotransferase concentrations, and an increased activated partial thromboplastin time were observed. In a phylogenetic analysis, the isolate clustered close to a strain derived from South Korea. Conclusions: This is the first case of SFTSV infection with CNS disturbance in Dongyang, Zhejiang Province, China. The surveillance of suspected cases of SFTS is important in SFTSV endemic regions.